Introduction to imagery training in working with swimmers by using the Sports Imagery Ability Measure (SIAM) - Stępniak, Małgorzata; Budnik-Przybylska, Dagmara (Journal of Education, Health and Sport, 2017)
Introduction Imagery training plays an important part in the interventions that help athletes improve their athletic performance. It is an effective technique listed in the most of the models of athletes’ mental preparation. Imagery training, which in some sources is called visualization (although visualization refers to the visual channel, but imagery includes all sensory modalities) is a process that recreates experiences that already exist in memory (Karageorghis and Terry, 2014). Aim of the study This work is an introduction to the imagery training of two young swimmers by using the SIAM. Material and method Two female 12 years old athletes of swimming participated in the study. These athletes regularly take part in competitions and psychoeducation classes related to mental training. In the pre-test the Sports Imagery Ability Measure (SIAM) was used, which measures the imagery ability and the post-test was completed after the workshops concerning introduction to imagery in sport. Results In both athletes the results in the Sports Imagery Ability Measure (SIAM) increased in all subscales. Conclusions The results obtained by the athletes in the pre- and post- tests indicate that the psychological training resulted in the intended outcome.